Top Management Characteristics and Earnings Management Strategies: Evidence from Indonesia - Nurmayanti, Poppy; Indrawati, Novita; DP, Emrinaldi Nur (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study examines whether the strategic choice of earnings management chosen by top management (such as CEO and CEO and a team separately) is related to characteristics of top management (i.e., genders, age, tenure, financial expertise, business experience, and education). This study employs regression analyses to analyse 707 firm-year observations of manufacturing companies listed in the Indonesian Stock Exchange (IDX) between 2010 and 2018. This study found that top management team tended to choose the strategic choice of real-based earnings management. Meanwhile, top management individually, both CEO and CFO tend to choose accrual earnings management strategies over real activity-based earnings management. These results are inline with upper echelon theory and financial reportpreparation and mechanism in companies, especially in selecting and appointing top-level executive.